Aurintricarboxylic Acid Suppresses Hepatitis B Virus Replication by Inhibition of RNase H Activity - Xu, Meng; Guan, Xiao (Frontiers in Virology, 2022)
Background: Chronic hepatitis B virus (HBV) infection is a global health threat, for which there are urgent needs to develop novel therapeutics. Methods: The aurintricarboxylic acid (ATA) has been demonstrated with broad-spectrum antimicrobial and antiviral activities. In this study we implemented ATA treatment in HBV-infected and -transfected hepatocytes to uncover whether ATA inhibits HBV replication and its underlying mechanism. Results: HBV DNA levels were significantly reduced while viral proteins or transcripts were not altered. In contrast, ATA treatment did not further deteriorate HBV DNAs, viral proteins and transcripts in hepatocytes transfected by an HBV RNase H dead mutant. Moreover, ATA showed an inhibitory effect on DNA synthesis in hepatocytes transfected with lamivudine-resistant HBV mutants. Conclusions: ATA is a potent inhibitor of HBV replication by disrupting the RNase H activity of viral polymerase.